1984
DOI: 10.1111/j.1440-1827.1984.tb07646.x
|View full text |Cite
|
Sign up to set email alerts
|

Argyrophil Cells in the Urachal Epithelium and Urachal Adenocarcinoma

Abstract: Urachal adenocarcinoma, normal urachus, and urinary bladder were studied by histochemichal methods and electron microscopy. Many argyrophil cells were found in urachal adenocarcinoma and urachal epithelium. Autofluorescence and immunoperoxidase examinations showed that the argyrophil cells possessed serotonin, glucagon, and secretin. Some of the carcinoma cells and urachal epithelial cells contained fairly large amount of mucosubstances. On the other hand, only a few argyrophil cells and very weakly PAS positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Failure of adenocarcinoma of the bladder to express CEA is suggestive of a primary origin, but most tumours, primary or secondary, are CEA positive. The expression of NSE and chromogranin by cells of primary vesical and urachal adenocarcinomas is in keeping with reports of a neuroendocrine cell population in such tumours 26,27 and is not useful for differential diagnosis. The lack of any reliable morphological, immunophenotypical, or ultrastructural 28 difference between primary and secondary vesical adenocarcinoma may reflect the development of vesical adenocarcinoma from areas of intestinal metaplasia which become dysplastic and then invasive, a hypothesis supported by the expression of distinctive colonic epithelial markers in urachal and bladder adenocarcinomas.…”
Section: Discussionsupporting
confidence: 81%
“…Failure of adenocarcinoma of the bladder to express CEA is suggestive of a primary origin, but most tumours, primary or secondary, are CEA positive. The expression of NSE and chromogranin by cells of primary vesical and urachal adenocarcinomas is in keeping with reports of a neuroendocrine cell population in such tumours 26,27 and is not useful for differential diagnosis. The lack of any reliable morphological, immunophenotypical, or ultrastructural 28 difference between primary and secondary vesical adenocarcinoma may reflect the development of vesical adenocarcinoma from areas of intestinal metaplasia which become dysplastic and then invasive, a hypothesis supported by the expression of distinctive colonic epithelial markers in urachal and bladder adenocarcinomas.…”
Section: Discussionsupporting
confidence: 81%
“…2,[6][7][8][9] Only a handful of cases regarding mixed tumors with an adenocarcinomatous and a neuroendocrine tumor originating in the urinary bladder are reported, though some of them even arose from the urachus epithelium. [10][11][12][13][14] Due to the rarity of these tumors in the urinary bladder, no data with reference to their origin in this organ exist.…”
Section: Discussionmentioning
confidence: 99%
“…They also could detect extensive intestinal metaplasia and cystitis glandularis. 11 Abenoza et al, 10 Hom et al, 13 and Satake et al 14 each reported a case of an AC with a neuroendocrine component arising in the urachus. However, they did not find or rather mention a precursor lesion.…”
Section: Discussionmentioning
confidence: 99%
“…7 The frequent association of this tumor with other histologic variants supports these theories. 12 A third theory is a malignant transformation of neuroendocrine cells, which have been demonstrated in normal 17 and metaplastic bladder mucosa. 20 Our two cases, showing mixed histologic patterns, seem to support the first and second of these theories.…”
Section: Discussionmentioning
confidence: 99%